Reproductive Characteristics and Nutritional Status of Coastal Women - Nuruzzaman, -; Alam, Md Ashraful; Sharif, Md Parvez Iqbal; Akter, Parveen; Mazid, Nabeela; Anwar, Shah Niaz Md Rubaid (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Women are more vulnerable in health and family planning and this vulnerability is more indepth in coastal area. The study was done to determine the reproductive characteristics and nutritional status of women in coastal area. It was conducted in Moheshkhali upazila of Coxs Bazar district in 2013 among 220 purposively selected coastal women of reproductive age. Face to face interview was done through pretested questionnaire. Average age of the respondents was 26.5 years. Almost 60% of them were Muslims and 44% were illiterate. The average monthly family income and family size was Tk-6968.18 and 5.8 respectively. More than half (56%) of the respondents had history of regular use of contraceptives and oral pill was the most common type of contraceptive. Average number of children was 2.95. More than half of them (54%) had history of home delivery. More than one-third (34%) of them were under nourished. Nutritional status was significantly associated with income (p<0.05). Majority of them got early marriage (70%) but early marriage was not significantly associated with their nutritional status. Age at first pregnancy and parity of the respondents were in significant state with the nutritional status of women of coastal area (p<0.05). Socio-demographic disparity should be reduced to improve the nutritional status by improving the reproductive health of coastal women. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22881 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 38-41